2013
DOI: 10.1155/2013/752760
|View full text |Cite
|
Sign up to set email alerts
|

Approximate Solution of LR Fuzzy Sylvester Matrix Equations

Abstract: The fuzzy Sylvester matrix equationAX~+X~B=C~in whichA,Barem×mandn×ncrisp matrices, respectively, andC~is anm×nLR fuzzy numbers matrix is investigated. Based on the Kronecker product of matrices, we convert the fuzzy Sylvester matrix equation into an LR fuzzy linear system. Then we extend the fuzzy linear system into two systems of linear equations according to the arithmetic operations of LR fuzzy numbers. The fuzzy approximate solution of the original fuzzy matrix equation is obtained by solving the crisp li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This matrix equation contributed significantly in control theory (Benner 2004;Darouach 2006). A study was conducted by Shang et al (2015), who applied a concept of arithmetic multiplication operator previously demonstrated by Dehghan et al (2006)and Guo and Shang (2013) in solving FFLS and FME respectively. This operator converts the FFSE into a crisp form of Sylvester matrix equation where the solutions are then obtained using the Kronecker product of matrices where the multiplication operator provided the simpler method which is easy to handle by most of the researchers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This matrix equation contributed significantly in control theory (Benner 2004;Darouach 2006). A study was conducted by Shang et al (2015), who applied a concept of arithmetic multiplication operator previously demonstrated by Dehghan et al (2006)and Guo and Shang (2013) in solving FFLS and FME respectively. This operator converts the FFSE into a crisp form of Sylvester matrix equation where the solutions are then obtained using the Kronecker product of matrices where the multiplication operator provided the simpler method which is easy to handle by most of the researchers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, alternative methods for solving FFSME have been proposed by (Malkawi et al 2015c). Contrary to (Guo and Shang 2013), their research shows that FFSME is converted to FFLS using the Kronecker product and applying their proposed linear system method. In (Malkawi et al 2014), the FFLS was transformed to a linear systems where the solution is obtained by the matrix inversion method.…”
Section: Introductionmentioning
confidence: 99%
“…To date, considerable work has been conducted on matrix equations, such as the fuzzy matrix equation (FME), AX m =B m [17], and fuzzy Sylvester matrix equation (FSE), AX +XB =C [2,15,16,18,19,27].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, some researchers paid more attention to LR fuzzy linear systems. In 2013, Guo and Shang [22] proposed a computing method for the fuzzy Sylvester matrix equations +̃=̃with LR fuzzy numbers. Later, Gong et al [23] studied the general dual fuzzy linear matrix systems̃+̃= +̃based on LR fuzzy numbers.…”
Section: Introductionmentioning
confidence: 99%